Validation of the repetitions in reserve rating scale in Paralympic powerlifting athletes - Neto, F. R.; Dorneles, J. R.; Aidar, F. J.; Gonçalves, C. W.; Veloso, J.; Costa, R. R. G. (International Journal of Sports Medicine, 2022)
The present study aimed to validate the perceived exertion scale based on the repetitions in reserve (RIR) of Paralympic Powerlifting (PP) athletes. Twenty-one PP athletes were assessed in the one-maximum repetition test (1RM) of the bench press exercise, maximum repetition strength tests with loads corresponding to 90, 85, 80, and 75% of 1RM, and 4-repetitions strength tests (4-repST) with 100, 90, 85, 80, and 75% of the 1RM. The RIR scale was assessed after each set of the 4-repST and compared to the 1RM and maximum strength tests. For criterion validity, the total estimated repetition was significantly lower compared to the maximum strength test repetitions in the lower scores of the RIR scale (median=7.0 vs. 9.0 for 75% of 1RM). The total estimated repetition correlation with maximum strength was very high and significant (ICC=0.91). Using the Bland and Altman method, the difference between means was 0.9 reps, and the interval around differences was 6.4 reps. For construct validity, and the RIR scale presented high correlation with 1RM intensities (rho=0.86, p=0.05). The RIR scale was validated and coaches and sports trainers can use this monitoring tool to ensure submaximal loads when improving lift technique, which is extremely rigorous in PP.